Assessing quality and productivity of journal publications using a bibliometric analysis: A platform towards world class education - Taib, Che Azlan; Mohammed, Ahmed Hani (2018)
The aim of bibliometric analysis is to statistically assess scientific literature in a given field so much so that its applicability to various disciplines is evident.This paper presents the outcomes of a Bibliometric analysis aiming to gauge knowledge quality and productivity of UUM‟s Journal of Information and Communication Technology (JICT), a refereed journal in the field of social sciences.This study called temporal evolution where information such as year of publication, number of articles, and the comulative percentage has been analyzed. A total of 122 articles were reviewed.Out of this figure, 41.4% were the works of UUM lecturers while the remaining numbers were produced by authors from other institutions.Diversification of contributors was also apparent with authors coming from many different countries such as United Kingdom, New Zealand, Iran, Singapore and Jordan, just to name a few.Compositions of author are also varied. Off all the articles analyzed, 10.7% are single authored, 30.33% dual authorships, 37.7% tripartite contributors, and the remaining 19% has more than four authors. In terms of institution, the five most productive are UUM (45%), UPM (11.5%), UKM (9%), UTM (8.2%), and UiTM (7.4%). Other notable institutional contributors are MMU (5.8%), USM (5.0%), UniMAP (3.3%), as well as UMP, IIUM, Institute Basic Science and Federal University of Technology with 2.5% contributions each.At the end of the study, concluding remarks and further research recommendations are discussed.